Reviewing the Impact of Land Use and Land‐Use Change on Moisture Recycling and Precipitation Patterns - te Wierik, Sofie A.; Cammeraat, Erik L. H.; Gupta, Joyeeta; Artzy‐Randrup, Yael A. (Water resources research, 2021)
Green water, or plant‐available soil moisture, is a substantial subset of terrestrial fresh water. Land‐use change (LUC) alters green water dynamics through interactions on the micro‐level (i.e., between the soil and vegetation) and on the macro‐level (i.e., between the land surface and atmosphere). Ongoing global deforestation, and growing interest in reforestation projects, begs the question whether such large‐scale LUCs have major eco‐hydrological impacts via the process of terrestrial moisture recycling. This requires a systematic, mechanistic understanding of green water dynamics in relation to LUC. Hence, this literature review addresses the above question via a scoping review that draws from papers covering empirical observations and simulated approximations on the hydrological effects of LUC from different parts of the world. The results show that some regions are more vulnerable to LUC than others and can affect local as well as distant hydrology of landscapes. Furthermore, we find that many studies focus on the global level or on tropical rainforests, through which we identify a knowledge gap for temperate regions and drylands. We derive analytical tools and directions for further research that can improve understanding of the effects of LUC on moisture recycling patterns to minimize unexpected hydrological impacts for nature and society. Key Points Advanced understanding of the effects of land‐use change on moisture recycling patterns demands an overarching review on this issue Spatial and temporal patterns of moisture recycling are highly variable, but the hydroclimatic effects of land‐use changes on these patterns remain—although sensible considering the processes of scale and uncertainties due to water's active role in the atmosphere—under‐researched There is a need to increase our understanding of context‐specific land‐use change effects on moisture recycling dynamics via case study research to evaluate potential hydroclimatic effects and prevent unintended consequences on water resources